POLICY PERFOEMANCE DALAM VAKSINASI MASSAL COVID-19 DI KOTA PEKANBARU PADA TAHUN 2021 - Siti Rahayu; Zulfa Harirah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Covid-19 vaccination program is one of the policies issued by the Pekanbaru City government in dealing with Covid-19. It is hoped that this program can cover the people of Pekanbaru City and be accepted by the community. However, the Covid-19 vaccination has not been evenly distributed due to public distrust of the Covid-19 vaccination, in this case it can be judged that the community does not know and understand the importance of vaccination in dealing with the Covid-19 outbreak. Furthermore, the data collection techniques used are interviews and documentation. While the data source used is primary data obtained from the research location in the form of research informants and supported by secondary data, namely documents related to interviews, observations, and document studies. The location of this research is in the city of Pekanbaru. The results of the research carried out are that the Policy Performance in the Covid-19 mass vaccination in Pekanbaru City in 2021 has been carried out in accordance with the 2021 Pekanbaru City Regulation in paragraph 17A, starting from setting and collecting data on the target recipients of Covid-19 vaccinations. The Policy Effect, namely the target coverage and comparisons have not been achieved, the deviation bias exists, access to affordable locations, communication is not good and access is equal, and the suitability of the program to the needs of the community is appropriate. In Policy Impact, the dimensions of the initial results of policy outputs are appropriate, the medium term is appropriate and the long term is appropriate. Keywords: Policy Performance, Policy Effect, Policy Impact